2022
DOI: 10.3390/nu14030483
|View full text |Cite
|
Sign up to set email alerts
|

From the Bench to the Bedside: Branched Amino Acid and Micronutrient Strategies to Improve Mitochondrial Dysfunction Leading to Sarcopenia

Abstract: With extended life expectancy, the older population is constantly increasing, and consequently, so too is the prevalence of age-related disorders. Sarcopenia, the pathological age-related loss of muscle mass and function; and malnutrition, the imbalance in nutrient intake and resultant energy production, are both commonly occurring conditions in old adults. Altered nutrition plays a crucial role in the onset of sarcopenia, and both these disorders are associated with detrimental consequences for patients (e.g.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 175 publications
1
17
0
Order By: Relevance
“…In our previous work, we demonstrated that mitochondrial function in PBMCs from old malnourished patients can be boosted with targeted nutritional support and that this activity is correlated with improvement in clinical outcomes [30]. Our data suggest that mitochondrial dysfunction may be considered a hallmark of frailty and targeted as a possible therapeutic intervention [19]. Mitochondrial function is correlated with muscular strength, performance and mass, and these are key features of sarcopenia, which is associated with physical frailty [27,56].…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In our previous work, we demonstrated that mitochondrial function in PBMCs from old malnourished patients can be boosted with targeted nutritional support and that this activity is correlated with improvement in clinical outcomes [30]. Our data suggest that mitochondrial dysfunction may be considered a hallmark of frailty and targeted as a possible therapeutic intervention [19]. Mitochondrial function is correlated with muscular strength, performance and mass, and these are key features of sarcopenia, which is associated with physical frailty [27,56].…”
Section: Discussionmentioning
confidence: 62%
“…The decrease in naïve T cells during aging may lead to the reduced abilities of older patients to respond to unknown immune stimuli, leading to increased susceptibility to infections and cancer and reduced immune response to vaccines [14][15][16]. The impairment of mitochondrial function associated with aging [17] has been proposed as one of the main contributors to the development of immunosenescence and immune system dysfunction [18][19][20]. Immunosenescence and immune cell mitochondrial dysfunction may be the cause of the increase in sterile inflammation associated with aging named "inflammaging" [21,22].…”
Section: Introductionmentioning
confidence: 99%
“…57 It is suggested that amino acid infusion might counteract the development of sarcopenia by stimulating protein anabolism. 58 Another potential benefit of amino acid infusion is protecting the kidney, which is one of the most affected organs in SAP. 59 Animal models have demonstrated an increase in renal blood flow in response to a shortterm amino acid infusion, 60 and this was confirmed in the Nephro-Protective Trial showing that amino acid infusion could increase estimated glomerular filtration rate and urine output in critically ill patients.…”
Section: Protein Delivery In Pnmentioning
confidence: 99%
“…Furthermore, branched‐chain amino acids can enhance mitochondrial function and reduce oxidative stress, especially when patients are in a protein catabolic state, such as the early phase of SAP 57 . It is suggested that amino acid infusion might counteract the development of sarcopenia by stimulating protein anabolism 58 …”
Section: Introductionmentioning
confidence: 99%
“…Diets that accentuate protein and antioxidants may combat sarcopenia by increasing muscle mass and strength via improved protein homeostasis and autophagy (the orderly degradation and recycling of cellular components) as well as reduced oxidative stress ( 120 ). Likewise, branched-chain amino acids, polyunsaturated fatty acids, selenium, vitamin D, and zinc can reduce oxidative stress, support mitochondrial homeostasis, and mitigate low-grade inflammation, thus suggesting their potential roles in the treatment of sarcopenia ( 128 ). To the contrary, however, a Mendelian randomization analysis shows little effect from these nutrients with the exception of a genetically high concentration of serum iron, which increased sarcopenia risk ( 129 ).…”
Section: Nutritional Therapy In Patients With Acute Covid-19 T2d and ...mentioning
confidence: 99%